Intersectoral Competition for Water Between Users and Uses in Tamil Nadu-India - Suresh, S. (Frontiers in Earth Science, 2021)
Abstract: Water is a manageable asset for drinking, food creation and industry and its need increment as the populace increments. Water for irrigated agriculture, industry and domestic needs in India will go up to 1072, 130 and 102 billion m3 (BCM) in the year 2050. In the state of Tamil Nadu, the water needs during 2025 for irrigation, domestic, livestock and industrial sectors are 52.7, 1.5, 1 and 2 billion m3 respectively against the available supply of 24.6 BCM of surface water and 23 BCM of groundwater during the same period. Though these statistics an easy balance between need and supply, it is often not the case. By the year 2050, some 60 per cent of the world’s people will live in cities. In India and Tamil Nadu 38 and 48 per cent of the people will live in cities. Tamil Nadu is the second most urbanized state in India with 48 per cent of its population living in cities. This urban push shall demand a large share of the common water resources and most of the reservoir systems shall be facing increased water demand for non-agricultural purposes, bringing in imbalances in other sectors namely agriculture. Contrary to mounting demand, the growing need for water is however, difficult to deal with. Further there are social and environmental costs in terms of diversion of water from agriculture to urban uses. Also, the discharge of sewage and industrial effluents pollutes surface and ground water affecting not only human health but also the entire ecosystem. Therefore, this paper examines the water management challenges in Tamil Nadu, India with respect to meeting future water demands across competing sectors.